(untitled) (Texas Journal of Engineering and Technology, 2023)
This article provides an in-depth overview of genetic counseling, its methods, and its impact on patients and families. Through a thorough literature analysis, we explore the evolving landscape of genetic counseling, its challenges, and the role of emerging technologies. The methods section details the genetic counseling process, and the results section highlights the significant benefits and challenges. In the discussion, we address the ethical and societal implications, concluding with suggestions to improve and expand the field of medical genetic counseling.